Diseño de una micro central hidroeléctrica para la Reserva Biológica Alberto Manuel Brenes - Rodríguez Rojas, Lee Marvin (2013)
The micro-hydroelectric power station design for the Alberto Manuel Brenes Biological Reserve of the University of Costa Rica, located in Los Angeles de San Ramón, Alajuela, has been made because the existing hydroelectric plant does not meet the current energy requirements in the area. The object of this project is to design an optimal hydroelectric generator system to meet the energy needs of the Reserve. To make the project in an efficient and reliable way, able to supply as much as possible the energy needs of the Reserve, the first step was to analyze the existing site electrical installations and equipment, resulting in an electrical peak power demand of 5,5 kW, that is achieved with a change in the consumption behavior and in the type of lighting used. The hydraulic potential of the San Lorencito river was calculated, using the indirect method of flows correlation and direct measurements on the site, obtaining a variable curve between 53 l/s and 212 l/s. Height, gross and net, was defined by direct measurement to design the intake works, the penstock and the powerhouse. An economic feasibility study was made, which shows the profitability of developing the project in relation to the cost of install public electrification or placing a thermal plant. The considered appropriate location of the water intake is placed 320 m from the powerhouse, which will remains in the same place, resulting in 18,81 m of gross head. Design is such made that the intake is protected against floods and doesn't allow unwanted objects entering the system. The design has two proposals: The first one is to get the most amount of energy available from the San Lorencito Station (8 kW), placing a completely new pipeline of DN250 PVC size tube with a design flow of 130 l/s (with a 60% of the time availability). The second one is to supply only the energy required by the Station (5 kW), extending the current DN200 size pipeline to the proposed intake setting a new stretch...